Resíduos Glass waste as an alternative aggregate or binder in the production of cement artifacts - Schneider, Roselene Maria; Amaral, Adriana Garcia do; Souza, Marcos Ferreira de (Revista Nacional de Gerenciamento de Cidades, 2023)
This article aims to provide an overview of the current state of utilizing glass in the production of artifacts for civil construction. Specifically focusing on glass waste, existing literature presents numerous studies indicating the technical feasibility of incorporating glass into products used in the civil construction field, as discussed in the development of this material. This study conducted a comprehensive literature review to report the latest advancements in the post-use glass chain, primarily emphasizing reuse and integration into civil construction artifacts while discussing the advantages and disadvantages of this process. The reviewed works were sourced from databases such as Scielo, Science Direct, Periódicos Capes, etc. The utilization of glass waste in the production of civil construction artifacts holds great promise, as it allows for the substitution of a portion of both fine and coarse aggregates. Therefore, the incorporation of glass contributes to various aspects, particularly in addressing environmental concerns. The main observed factors that influence the physical and chemical characteristics include the particle size distribution of the glass, the quantity of glass used, and the moisture content of the mixture. The utilization of glass waste in different particle sizes demonstrates an increase in pozzolanic activity as the particle size decreases, with the physical properties of the resulting products being more significantly affected by particle size rather than the quantity of waste used in concrete or mortar.